The Berlin mission : the American who resisted Nazi Germany from within - Breitman, Richard, 1947- (Public Affairs, 2019)
In 1929, Raymond Geist went to Berlin as a consul and handled visas for emigrants to the US. Just before Hitler came to power, Geist expedited the exit of Albert Einstein. Once the Nazis began to oppress Jews and others, Geist's role became vitally important. It was Geist who extricated Sigmund Freud from Vienna and Geist who understood the scale and urgency of the humanitarian crisis. Even while hiding his own homosexual relationship with a German, Geist fearlessly challenged the Nazi police state whenever it abused Americans in Germany or threatened US interests. He made greater use of a restrictive US immigration quota and secured exit visas for hundreds of unaccompanied children. All the while, he maintained a working relationship with high Nazi officials such as Heinrich Himmler, Reinhard Heydrich, and Hermann Göring. While US ambassadors and consuls general cycled in and out, the indispensable Geist remained in Berlin for a decade. An invaluable analyst and problem solver, he was the first American official to warn explicitly that what lay ahead for Germany's Jews was what would become known as the Holocaust.